Effects of South-to-North Water Diversion Project Cascade Dams on Riparian Vegetation Along the Middle and Lower Reaches of the Hanjiang River, China - Yang, Jiao; Li, En-Hua; Yang, Chao; Xia, Ying; Zhou, Rui (Frontiers in Plant Science, 2022)
The influence of the construction of dams for water diversion on the ecological environment has attracted recent widespread attention. Over time, dams have emerged as one of the most important factors affecting the vegetation along the riparian zones of rivers. To elucidate the effects of cascade dams on riparian vegetation along the middle and lower reaches of the Hanjiang River, we examined riparian vegetation types upstream and downstream from dams. A total of 14 sample sites and 131 quadrats perpendicular to the river were investigated in June 2019, and 14 sample sites and 134 quadrats were investigated in October 2019. The riparian vegetation was divided into 15 (in June) and 11 (in October) vegetation types by two-way indicator species analysis (TWINSPAN). Significant differences were found between the vegetation types upstream and downstream of dams. Redundancy analysis (RDA) showed that soil moisture content, distance from the water, altitude and soil total nitrogen (TN) were the main environmental factors affecting plants distributions, and soil moisture content was the main factor affecting the zonal distribution of vegetation. By analyzing the impact of cascade dams on the hydrological regime, we found that the construction of cascade dams led to the differentiation of vegetation types upstream and downstream of the dam, and the riparian habitats were fragmented by these dams. This study provides both an important reference for the protection of riparian vegetation and riparian ecosystems and a basis for the management and restoration of river ecosystems after the construction of cascade dams.